North-West Province, South Africa: Communal and commercial livestock systems in transition - Galvin, K.A.; Thornton, Philip K.; Boone, Randall B.; Knapp, L.M. (Springer, 2008)
South Africa is a nation rich in natural resources, from diamonds and gold, to the world-famous fauna in Kruger and other national parks, to areas of extreme diversity in flora (the southern coast of South Africa is rich in plant species) (Kemper et al. 1999). South Africa is also home to 43 million hectares of savanna, contributing to Africa possessing the world’s highest proportion of these savannas (Hudak 1999). But what is the state of South Africa’s savanna ecosystems? Multiple studies show that land degradation in the country as a whole is extremely high (Dean and Macdonald 1994, Snyman 1998, Hoffman and Todd 2000, Dube and Pickup 2001) and that livestock carrying capacities on rangelands are decreasing (Dean and Macdonald 1994). What are the causes for this decline in rangeland sustainability and productivity? A long process of land fragmentation is certainly one reason.